KUALITAS PELAYANAN PUBLIK DI KANTOR KELURAHAN KARANG ASAM ILIR KOTA SAMARINDA - Chairi, Minal; Irawan, Bambang; Rande, Santi (Magister Administrasi Publik FISIP Universitas Mulawarman, 2023)
This article wants to describe the quality of public services in the Karang Asam Ilir Village Office, Sungai Kunjang District. A qualitative approach with a descriptive research model as a research method. Interviews, observations, and field studies were used to obtain research data which were then analyzed using an interactive data analysis model. Testing the validity of the data is done by testing the reliability and validity of the data. In general, the quality of public services in Karang Asam Ilir Village is good. Three of the five dimensions of service quality have fulfilled the requirements of good public service. The dimensions that have been achieved include the dimensions of assurance, responsiveness, and empathy. The other two dimensions have not been achieved, namely the dimension of reliability and the dimension of physical or tangible evidence. Supporting factors consist of SOP, Collaboration with Related Services, Budget Availability, and Employee Rolling System. Inhibiting factors aspects of human resources, facilities and infrastructure.Keyword : service quality, physical evidence, reliability, assurance, responsiveness, empathy